Equity Crowdfunding: The Secondary Market’s Implementation and Legal Protection for Investors Using Technology-Based Crowdfunding: Comparative Study of Indonesia – United States of America - Hanifiansyah Ilham Nugroho (Pancasila and Law Review, 2023)
The secondary market in equity crowdfunding aims to facilitate Investors in trading their Micro, Small, and Medium Enterprises (MSMEs) shares to other Investors as an exit and entrance strategy for interested Investors. Therefore, the traded shares must be liquid, ensuring that the secondary market of equity crowdfunding operates fairly, orderly, and efficiently. However, implementing the secondary market in equity crowdfunding in Indonesia, introduced in 2018 by the Financial Services Authority (OJK), still leaves room for evaluation and improvement. This thesis first examines the organization of the secondary market in Indonesia, which lacks legal certainty for both the Organizer and Users. Secondly, it explores the regulations on the secondary market in equity-based Crowdfunding in the United States, which can be used as a reference to develop legal regulations in Indonesia, including the prohibition of share sales in the first year and the classification of equity-based Crowdfunding for startup companies and medium-sized enterprises. Thirdly, applying American laws in the Indonesian legal framework can provide greater financial stability for issuing companies and reduce the risk of bankruptcy for Investors in equity-based Crowdfunding. The research findings indicate that the management and philosophy of the secondary market in equity crowdfunding cannot be equated with a Stock Exchange. Preventive legal protection for Investors can be provided through guidelines issued by the OJK, such as auto-reject limits, standardized buying and selling mechanisms, trading hours, transaction fees collected by the Organizer, transparency of daily transaction summary data, and mechanisms for determining the fair share price in initial trading on the secondary market. There are criminal and administrative sanctions for repressive legal protection.